توظيف مربيات التربية التحضيرية للألعاب الحسية والحركية لتنمية الانتباه لدى أطفال ما قبل المدرسة - عتروس هيثم; عزرور لبنى (University of Eloued جامعة الوادي, 2024)
Abstract: The study aimed to identify the reality of employing kindergarten teachers in preparing sensory and motor games to develop attention in preschool children in some primary schools in Annaba municipality; through answering the following two questions: 1-What is the role of teachers in employing sensory-motor games to develop the ability to focus, increase attention span, and flexibility in shifting attention in preschool children in the primary schools of Annaba municipality? 2-What are the competencies of teachers in planning, implementing and evaluating sensory and motor games to develop attention in preschool children in the primary schools of Annaba municipality ? The descriptive approach was adopted, and the study sample consisted of (50) kindergarten teachers. A questionnaire consisting of (34) items was used, distributed over two axes: the axis of teachers' competencies in planning, implementing and evaluating sensory and motor games, and the axis of the role of teachers in employing sensory-motor games to develop attention. The results indicated that the employment of these games by teachers was high on the total questionnaire; where the competencies axis ranked first, followed by the axis of the teacher's role in employing these games to develop attention. The study concluded with some recommendations and suggestions in light of the results. ملخص: هدفت الدراسة إلى معرفة واقع توظيف مربيات التربية التحضيرية للألعاب الحسية والحركية لتنمية الانتباه لدى أطفال ما قبل المدرسة ببلدية عنابة. اعتمد المنهج الوصفي، وتكونت عينة الدراسة من (50) مربية، واستخدمت أداة الاستبانة المكونة من (34) عبارة، موزعة على محورين. ودلت النتائج على أن توظيف المربيات لتلك الألعاب كان مرتفعا على إجمالي الاستبانة؛ حيث احتل محور الكفايات المرتبة الأولى، يليه محور دور المربية في توظيف تلك الألعاب لتنمية الانتباه. وقد ختمت الدراسة ببعض التوصيات والاقتراحات في ضوء ما أسفرت عنه من نتائج.
مدارس بلدية عنابة نموذجا
Keywords: الألعاب الحسية الحركية; الانتباه; طفل ما قبل المدرسة; مربية طفل ما قبل المدرسة; التربية التحضيرية; Sensory motor games; attention; preschool child; preschool teacher; preparatory education